STRATEGY OF FARMER WOMEN GROUP THROUGH OPTIMIZATION OF EMPTY LAND UTILIZATION WITH PLANTING SEEDS IN PIPITAN VILLAGE, SERANG CITY - Rika Kartika; Nani Rohaeni; Miftahudin Miftahudin; Ine Aprianti; Tri Indriyani (International Journal of Engagement and Empowerment, 2021)
The condition in Pipitan Village, which is the focus of this activity, is the Farmer Women Group "Srikandi Makmur Sejahtera" has not been established for a long time, so few activities have been carried out. Besides that, the existence of large areas of land, which are less productive. Based on these conditions, this activity aims to explore the farmer women group's potential and optimize the land by cultivating plant seeds. The results of the activities carried out are can exploring the potential of the Farmer Women Group and get productive land yields by planting plant seeds, which will get beneficial harvests